Comparison of Municipal and Kitchen Waste Leachates for the Production of Organic Acids and Polyhydroxyalkanoates (PHA) - Hamed, Jame'ah (2003)
The feasibility of using municipal solid waste leachate as carbon source for the production of polyhydroxyalkanoates (PHA) was investigated in this study. Leachates from MSW in Kuala Lumpur area were subjected to anaerobic treatment under specified condition for the production of organic acids. Two types of leachates were used, i.e. fresh leachate from the city council garbage trucks and combined leachate from several cells at the sanitary landfill. Initially, prior to the PHA production, the characteristics (pH, COD, BODs, ammonium, total solid, suspended solid, organic acids and heavy metals) of the municipal solid waste leachate were analysed. The effect of pH and inoculum on organic acids production during anaerobic treatment was evaluated. Treatments were carried out at 30°C for 7-10 days under different conditions of pH, i.e. uncontrolled pH, adjusted to initial pH 7, controlled at pH 7 for 24 hours, and continuous control at pH 7 and pH 5.5.The production of organic acids from fresh leachate was highest when the initial pH was adjusted to pH 7 with no further pH control. About 45 g/L total organic acids was produced, comprising of 28 g/L lactic acid, 8 g/L acetic acid and 9 g/L propionic acid. Based on the initial BODs, the organic acid yield was about 80%. In contrast, with the combined landfill leachate the highest organic acids obtained was only 14 gIL when the pH was controlled at pH 5.5, with acetic acid as the main product. Temperature at 37°C gave the highest production on the second day. When the fresh leachate was autoclaved and seeded with 10% fermented kitchen garbage, the highest organic acids achieved were between 34-37 g/L. The highest selectivity of lactic acid (85%) was achieved during treatment of fresh leachate seeded with kitchen garbage without any pH adjustment. Overall, the results showed that the fresh leachate could be effectively converted to 45 g/L total organic acids by anaerobic treatment when the initial pH was adjusted to pH 7. The supernatant collected from the treatment of highest organic acids production was used in the second stage for the production of polyhydroxyalkanoate (PHA). Ralstonia eutropha was used for the production of PHA using leachate as carbon source for the batch and fed-batch fermentation. In batch fermentation using shake flask, 3.4 g/L PHA was produced which gave 86% g PHAlg cell. In fed-batch fermentation the maximum PHA concentration was 6.9 g/L, corresponding to 85% (gig) of cell dry weight. The PHA produced was plastic-like and resembles low density polyethylene. Thus the fresh leachate proved to be a suitable carbon source for organic acids and subsequently used in PHA production.